Advanced nanostructured carbon-based materials for rechargeable lithium-sulfur batteries. (January 2019) - Zhang, Linlin; Wang, Yijing; Niu, Zhiqiang; Chen, Jun
Abstract: Lithium-sulfur (Li-S) batteries are attracting much attention due to their high energy densities. However, Li-S batteries often suffer from low Coulombic efficiency, severe degradation of cyclic capacity, and low utilization of active sulfur material because of the low electrical conductivity of sulfur and the severe shuttle effect. To solve these issues, various nanostructured carbon-based materials have been developed to serve as the sulfur host materials, modify separators and protect lithium (Li) anode due to their good conductivity, large surface area, and electrochemical stability. In this review, a brief introduction of electrochemical principles and prospects of the Li-S batteries are discussed firstly. Then the recent achievements and challenges of nanostructured carbon-based materials in Li-S batteries are summarized. The nanostructured carbon-based materials focus on active carbon, carbon nanotubes, graphene and their composites. The role of these carbon-based materials in Li-S batteries emphasize on the design of sulfur host materials, the modification of functional separators as well as the protection of the Li anode. Furthermore, various flexible Li-S batteries based on freestanding nanostructured carbon/sulfur electrodes are also presented. Finally, the further developments and prospects in this field are also discussed. Graphical abstract: Image